Does increasing the severity of penalties assessed in association with the 'zero tolerance for head contact' policy translate to a reduction in head impact rates in youth ice hockey? - Williamson, R. A.; Kolstad, A. T.; Nadeau, L.; Goulet, C.; Hagel, B.; Emery, C. A. (British Journal of Sports Medicine, 2021)
Background The risk of concussion is high in Canadian youth ice hockey. Aiming to reduce this burden, in 2011 Hockey Canada implemented a national `zero tolerance for head contact (HC)` policy mandating the penalization of any player-to-player HC. In 2018-20, Hockey Canada further amended this HC-policy including stricter enforcement of severe HCs.